EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN EDUCATION MOBILE PADLET TERHADAP HASIL BELAJAR IPA SISWA KELAS XI SMAN 1 GOWA - Akuarta, La Ode Reski; Nasir, Nasir; Akram, Akram (Universitas Muhammadiyah Makassar, 2025)
Education Mobile Padlet learning media is a collaborative learning platform that can be used as a medium in the teaching and learning process for digital learning media. This research aims to determine the effectiveness of using Education Mobile Padlet learning media on the science learning outcomes of class XI students at SMAN 1 Gowa. The research methodology used in this study is a quantitative experimental method, carried out using a pr-experimental design which was designed using a pretest-posttest method. The results of research and analysis of student learning through descriptive statistical analysis before using the Education Mobile Padlet learning media, the pretest result was 67.78 and the posttest result was 84.17. The results of the inferential analysis obtained t count = 74,114 t distribution table 1.690 with the calculation results t count > t table or 74,114 > 1.690, thus h0 is rejected and h1 is accepted. So it can be concluded that the use of Education Mobile Padlet learning media influences the learning outcomes of science students at UPT SMP Negeri 1 Gowa